2021
DOI: 10.1002/ps.6751
|View full text |Cite
|
Sign up to set email alerts
|

Current situation and forecasting of resistance evolution to lambda‐cyhalothrin in Spanish medfly populations

Abstract: BACKGROUND The control of the Mediterranean fruit fly Ceratitis capitata (Wiedemann) in Spanish field populations mainly relies on the insecticides lambda‐cyhalothrin and spinosad as bait sprays. However, their sustainable used is compromised by the development of lambda‐cyhalothrin resistance and the detection of spinosad resistant alleles. In addition, the use of lure‐and‐kill traps covered with deltamethrin has increased in the last years. It is thus urgent to predict the impact that the combination of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…An important component of IRM is the use of alternative insecticides to delay the onset of resistance to a particular insecticide and avoid the combined use of insecticides with cross-resistance. We have found deltamethrin resistance in geographic areas where lambda-cyhalothrin resistance already existed (Arouri et al 2015;Guillem-Amat et al 2022). Thus, it is possible that resistance to lambdacyhalothrin is conferring cross-resistance to deltamethrin, though they may also have evolved independently by different resistance mechanisms.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…An important component of IRM is the use of alternative insecticides to delay the onset of resistance to a particular insecticide and avoid the combined use of insecticides with cross-resistance. We have found deltamethrin resistance in geographic areas where lambda-cyhalothrin resistance already existed (Arouri et al 2015;Guillem-Amat et al 2022). Thus, it is possible that resistance to lambdacyhalothrin is conferring cross-resistance to deltamethrin, though they may also have evolved independently by different resistance mechanisms.…”
Section: Discussionmentioning
confidence: 85%
“…However, care should be taken when combining deltamethrin traps and lambdacyhalothrin sprays, since our results indicate that different scenarios of cross-resistance between these two pyrethroids may occur for Medfly populations in the area of study. Guillem-Amat et al (2022) simulated the evolution of lambda-cyhalothrin resistance under different crossresistance scenarios with deltamethrin and concluded that the efficacy of both pyrethroids would be seriously compromised under the assumption of cross-resistance, even when partial. Thus, farmers should avoid the overuse of both pyrethroids in the same fields for long periods of time, as there is a risk of cross-resistance between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations